ChemInform Abstract: The Synthesis, Structure and Properties of a New Compound with 1D Linear Chain Arsenomolybdate Anion Building Block. Issue 1 (17th December 2015) - Zhao, Wenqi; Su, Zhanhua; Zhao, Zhifeng; Cong, Bowen; Xia, Lin; Zhou, Baibin
Abstract: The new compound [Cu(bipy)]2 [H2 As2 Mo2 O14 ] is hydrothermally synthesized from a mixture of MoO3, CuCl2, Na3 AsO4, bipy, HCl, and H2 O (autoclave, pH 3.5, 160 °C, 6 d; 58% yield).